Analisis Kemampuan Guru SD Negeri 042 Rimba Makmur dalam Proses Belajar Mengajar Daring di Kecamatan Tapung Hulu Kabupaten Kampar - Yasa, Mila Puspita; Noviana, Eddy; Witri, Gustimal (Indonesian Research Journal on Education, 2022)
The COVID-19 pandemic has had a significant impact on the people of Indonesia. Especially in the aspect of education. This encourages the government to issue a policy that learning must be carried out online. Teachers are required to be able to carry out online learning as optimally as possible in order to achieve the expected learning objectives. This study aims to describe the cognitive, affective and psychomotor teachers of SD Negeri 042 Rimba Makmur in implementing online learning. Teachers' abilities in the cognitive, affective and psychomotor fields are good in carrying out online learning. Teachers already have the necessary facilities and infrastructure. In practice, it can be seen that the teacher is able to plan and carry out learning well, such as in the cognitive field, the teacher masters the concept of online learning materials, and uses several model questions such as objectives and essays during assigning assignments to students in addition to using methods, strategies, and approaches that are tailored to their students, while in the affective field in carrying out online learning the teacher has prepared everything such as preparing internet data/quota and using online learningmedia or tools. and prepare a set of teaching materials such as syllabus and online lesson plans.Meanwhile, in the psychomotor field, the teacher provides motivational words that build students'enthusiasm. In line with the results of the data analysis, it also shows that the ability of the teachers of SD Negeri 042 Rimba Makmur to get an average score of 82.4% percentage achievement and is included in the very high category.